Nonlinear Distortions in Electroacoustic Devices - DOBRUCKI, Andrzej (Archives of Acoustics, 2011)
The task of electroacoustic devices is a transmission of audio signals. The transmittedsignal should be distorted as little as possible. Nonlinear distortions are thedistortions depending on signal level. The types of nonlinear distortions as well astheir measures are presented in the paper. The weakest device in an electroacousticchain is a loudspeaker. It causes the greatest degradation of the signal. It is usuallythe most nonlinear part of the electroacoustic system. The nonlinearities in loudspeakersare described in details. Other types of nonlinear distortions as transientintermodulation in power amplifiers and distortions caused by the A/C samplingare also presented.